Conservation and restoration of Central European fens by mowing: A consensus from 20 years of experimental work - Hájková, Petra; Horsáková, Veronika; Peterka, Tomáš; Janeček, Štěpán; Galvánek, Dobromil; Dítě, Daniel; Horník, Jan; Horsák, Michal; Hájek, Michal (The Science of the total environment, 2022)
While the importance of conservation mowing for mesic grasslands is generally accepted, its use for fens and fen grasslands interspersed within agricultural land is still controversial. Although fens may persist naturally, ongoing environmental changes increase productivity and accelerate succession. These processes can be mitigated through conservation management with appropriate settings. However, long-term management experiments are challenging and provide only locally valid results. Here, we analysed vegetation data (bryophytes and vascular plants) from seven management experiments (spanning 3-20 years) conducted in Central European poor, moderately-rich, and calcareous spring fens (Czech Republic, Slovakia). Two of these experiments examined the effects of restoration of abandoned fens, while five experiments examined changes in mowing regimes in managed fens (cessation, intensification, delay to autumn, and litter removal). Data were analysed using unidimensional and multidimensional methods separately for the initial, extended, and entire period. Mowing had a statistically significant effect on species composition except for the shortest (3-year) experiment. Litter removal did not compensate for mowing. Mowing twice or delayed mowing significantly affected the species composition of calcareous fens. In all cases, cessation of mowing significantly reduced the richness of species, especially those of conservation importance. In contrast, any mowing of abandoned fens increased species richness. The effects of mowing intensification or cessation on species richness and composition of a restored calcareous fen were evident in the first 2-3 years. Other effects were initially weak or nonsignificant but later became stronger, such as mowing delay and restoration removal of litter, which became significant only after nearly 20 years. We found that cessation or restoration of mowing usually triggers a rapid vegetation change, whereas it can take decades to detect the response caused by changes in mowing timing. Importantly, mowing can stabilise or even restore vegetation of fen ecosystems that have been weakened by their fragmentation in the temperate agricultural landscapes.
Keywords: Vegetation change; Bryophyta; ekosystém; Consensus; Ecosystem; Permanent plot; biodiverzita; Litter removal; Biodiversity; Seasons; Management; Species richness; konsensus; roční období; Mires; zemědělství; Agriculture